A matter of time: study of circadian clocks and their role in inflammation. Issue 4 (8th February 2016) - Carter, Stuart J.; Durrington, Hannah J.; Gibbs, Julie E.; Blaikley, John; Loudon, Andrew S.; Ray, David W.; Sabroe, Ian
Abstract : Review of techniques used to study circadian rhythms and how the molecular clock influences immunity and inflammation. Abstract : Circadian rhythms regulate changes in physiology, allowing organisms to respond to predictable environmental demands varying over a 24 h period. A growing body of evidence supports a key role for the circadian clock in the regulation of immune functions and inflammatory responses, which influence the understanding of infections and inflammatory diseases and their treatment. A variety of experimental methods have been used to assess the complex bidirectional crosstalk between the circadian clock and inflammation. In this review, we summarize the organization of the molecular clock, experimental methods used to study circadian rhythms, and both the inflammatory and immune consequences of circadian disturbance.